Sistem Inventory Barang Bangunan Berbasis Web - Afni , Nurul; Wuryanto , Anus; Pujihastuti , Indhah (Journal of Students‘ Research in Computer Science, 2022)
TB. Barokah Jaya Group is a business engaged in trading with its operational activities selling building goods. Inventory of goods plays a very important role in managing the inventory of goods in the warehouse, has problems in managing inventory because it is still using a manual system. Often occurs when checking goods and errors in recording incoming and outgoing goods reports. We need a web-based application as a solution to existing problems using the PHP programming language and codeigniter as a framework. To run the web server the author uses XAMPP. As a result, store owners can check the availability of goods without having to go to the warehouse and manage incoming and outgoing goods by inputting goods data into the application that the author made, so that the results obtained are faster and more accurate